Challenges of investing in heritage in the development plan in Morocco: The case of the Taza region – Morocco - El Azzouzi, Younes (Journal of Humanities & Social Sciences, 2024)
The tangible heritage, which includes historical buildings, monuments, archaeological sites, and traditional arts, represents available resources that can contribute significantly to economic and social development processes. To preserve and value its cultural heritage, our country has launched many projects and initiatives supported by international bodies. This has enabled our country to learn about many elements of tangible and intangible cultural heritage at the international level, as well as to enhance its offers on cultural tourism. The city of Taza is considered one of the historical cities in the Kingdom, which is full of diverse material and intangible heritage, in addition to a diversity of cultural activities. such as cinema, theatre, audio-visual production, drawing and music, However it is still suffering at the level of local development from ways to integrate the cultural component into achieving economic recovery that benefits the region, and historical buildings exist in a deteriorating and rigid state awaiting destruction due to natural factors, While buildings need interventions from sector officials to integrate them and bring them out of the state of stagnation into a means of generating income.